Teaching Material Refirement Training Through the Making of A Mathematic Module for Teacher Working Group (KKG) Clutch 9 District Sukun, Malang City - Dyah Triwahyuningtyas; Prihatin Sulistyowati; Novia Eka Mahmuda (Jurnal Dedikasi, 2020)
Community service activities aim to compile a mathematics module to improve teacher performance as a form of professionalism in carrying out their profession. The refresher training activities for mathematics teaching materials and solving math problems for Elementary School Teachers in Cluster 9 Sukun District Malang were carried out well. There are three kinds of activities in the series, namely the lecture method by explaining the module material in detail, the second is the discussion method on the mathematics module material and the third practical exercises (drill practice) the teacher applies to compiling the module framework. Based on the pre-test score for filling in the module obtained 60.5% while the postest score obtained 80%, the training activity showed an increase of 42.5% so that it was said to be successful as seen from the increase in the module writing training. The results of the dedication activities show the teacher's ability to strengthen the material in making mathematics modules through lectures, discussions and practical exercises (drill practice)